Perbandingan Proses Pengisian SPT Tahunan antara Wajib Pajak Orang Pribadi dan Badan: Perspektif Magang di Kantor Konsultan Pajak Multi Sinergy Consultant - Mahardika, Tiska Ayu; Widajantie, Tituk Diah (VISA: Journal of Vision and Ideas, 2024)
The process of filling out the Annual Tax Return (SPT) is an important aspect of tax obligations for taxpayers, both individuals and business entities. This research aims to analyze the comparison of the annual SPT filling process between the two types of taxpayers, as well as identify the challenges faced by intern students and provide recommendations to improve student understanding. Using descriptive comparative methods, this research was conducted at the Multi Sinergi Consultant Tax Consultant Office. The research results show: 1) The process of filling out an individual's annual tax return focuses more on collecting personal documents and individual income: 2) filling in a corporate annual tax return includes a deeper understanding of the financial structure and accounting system of a business entity. Internship students often experience difficulties, especially in connecting information from the agency's financial reports with the requirements for filling out the Agency's Annual SPT. Recommendations include more integrated education between theory and practice, as well as relevant internship experience to increase students' understanding of the process of filling out annual tax returns.